PENARIKAN PEKERJA ANAK MELALUI PENDIDIKAN KESETARAAN STUDI PADA PERKUMPULAN LAMPUNG MEMBANGUN - Sudaro, Aye Sudarto; Imtihanah, Ani Nurul (Center of Gender Studies and Child of State Islamic Institute of Metro, 2021)
Abstract Based on the description of the agricultural sector in Indonesia in general and in particular Lampung, which certainly cannot be separated from the various risks of empirical findings related to child labor in the agricultural sector. It is deemed necessary to be able to provide breakthroughs and solutions in minimizing and even eliminating child labor in the agricultural sector. For this reason, what Lambang does is an effort to minimize and restore children to school and provide views and perspectives on families. Until the family can get out of economic misfortune. And deliver children to the maximum extent possible to get education in school. PKBM is an alternative for dropout children and some children who are constrained from continuing their education. PKBM is a non-formal education in which there is what is known as Package A which is equivalent to SD, Package B is equivalent to SLTP and Package C is equivalent to SLTA. PKBM school graduates are equivalent to SD, SLTP and SLTA education as it refers to the National Education Standards.